2009
DOI: 10.1007/s00248-009-9529-5
|View full text |Cite
|
Sign up to set email alerts
|

Linking Microbial Community Structure and Function to Seasonal Differences in Soil Moisture and Temperature in a Chihuahuan Desert Grassland

Abstract: Global and regional climate models predict higher air temperature and less frequent, but larger precipitation events in arid regions within the next century. While many studies have addressed the impact of variable climate in arid ecosystems on plant growth and physiological responses, fewer studies have addressed soil microbial community responses to seasonal shifts in precipitation and temperature in arid ecosystems. This study examined the impact of a wet (2004), average (2005), and dry (2006) year on subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
107
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(116 citation statements)
references
References 71 publications
6
107
1
Order By: Relevance
“…Also Shen et al (2008) and Tourna et al (2008) have found temporal shifts in archaeal abundance, and Stres et al (2008) and Tourna et al (2008) evidenced responsiveness of soil archaea to variations in soil temperature and soil moisture. Seasonal changes in soil climate were further closely linked to short-and medium-term variations in resource availability, which further correlated with the quantity and quality of organic matter entering the soil, as it was also previously suggested (Bell et al, 2009;Cookson et al, 2006;Krave et al, 2002). Consequently, total bacterial communities and individual phyla studied were clearly shaped by supply of DOC, DON and mineral N (that is, ammonia, nitrate), which is in agreement with previously published data (Drenovsky et al, 2004;Zak et al, 2003;Alden et al, 2001).…”
Section: Discussionsupporting
confidence: 79%
“…Also Shen et al (2008) and Tourna et al (2008) have found temporal shifts in archaeal abundance, and Stres et al (2008) and Tourna et al (2008) evidenced responsiveness of soil archaea to variations in soil temperature and soil moisture. Seasonal changes in soil climate were further closely linked to short-and medium-term variations in resource availability, which further correlated with the quantity and quality of organic matter entering the soil, as it was also previously suggested (Bell et al, 2009;Cookson et al, 2006;Krave et al, 2002). Consequently, total bacterial communities and individual phyla studied were clearly shaped by supply of DOC, DON and mineral N (that is, ammonia, nitrate), which is in agreement with previously published data (Drenovsky et al, 2004;Zak et al, 2003;Alden et al, 2001).…”
Section: Discussionsupporting
confidence: 79%
“…Increased water availability following rain events stimulated hydrolytic enzyme activities early in the monsoon season, and as the season ended, enzyme activities decreased back to pre-season levels. Similar pre-and post-monsoon season enzyme activities have been observed elsewhere in the Chihuahuan Desert (Bell et al 2009), but our enzyme measurements associated with individual rain events highlight how variable enzyme activities can be following rain events throughout the monsoon season. Changes in enzyme activities were similar following either large, infrequent or small, frequent precipitation regimes, but ratios between enzyme activities highlighted greater nutrient limitation following large, infrequent rain events.…”
Section: Discussionmentioning
confidence: 71%
“…Given that dryland systems are sensitive to changes in precipitation (HeislerWhite et al 2009, Thomey et al 2011, Sala et al 2012 it is unclear how availability of soil resources, often made available via extracellular enzymes, will change under future patterns of precipitation. A study by Bell et al (2009) in desert grassland found that EEA was similar at the beginning and end of the summer monsoon season, but enzyme dynamics following individual rain events across the season have not been determined. In this study, we experimentally altered the size and frequency of soil moisture inputs during the summer monsoon in a northern Chihuahuan Desert grassland and monitored extracellular enzyme potentials to examine how rainfall changes potential enzyme activities throughout the season.…”
Section: Introductionmentioning
confidence: 99%
“…In the SHP region, increases up to 37% has been found in EAs after only 2-3 rotations of sorghum with cotton (AcostaMartínez et al, 2011) and within two years following conversion from monoculture cotton to high input forage sorghum cropping systems without a change in soil organic C (Cotton et al, 2013). However, little is known about how these ecosensors respond to drought and whether soil type (e.g., differing textures) or management history affects the response under natural conditions in the field as most studies on the effects of drought and warming on soil EAs are conducted under simulated conditions (i.e., Sardans and Peñuelas, 2005;Bell et al, 2009). Under simulated drought conditions, soil EAs have shown a decrease as soil moisture is gradually reduced in native ecosystems in which other dynamics are involved (i.e., changes in plant physiology and biomass) (Sardans and Peñuelas, 2005;Sardans et al, 2008a,b).…”
Section: Introductionmentioning
confidence: 99%